Selection of morpho-agronomic descriptors for cupuaçuzeiro germplasm characterization - Alves, Rafael Moysés; Garcia, Antonio Augusto Franco; Cruz, Eniel David; Figueira, Antonio (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to select morphological and agronomic quantitative descriptors to characterize accessions of cupuaçuzeiro [Theobroma grandiflorum (Willd. ex Spreng.) Schum]. Fifty three descriptors were evaluated, including 14 from leaves, 18 from flowers, 16 from fruits, and 5 agronomic traits. To discard redundant or non-discriminating descriptors, a two step multivariate analysis of principal components was applied. The first phase included the selection of descriptors within each group of characteristics individually (leaf; flower; fruit; agronomic). Based on the descriptors selected in this first phase, a joined analysis of principal components for the final selection was done. Three criteria for variable exclusion were adopted. Thirty four descriptors were excluded, representing a reduction of 64%. A minimal list of descriptors for cupuaçuzeiro was proposed, including leaf length, leaf thickness, leaf apex width, leaf base vein angle, flower bud length, flower peduncle length, flower peduncle diameter, ovary girth, number of ovules, flower petal lamina length, staminode length, seed width, flat seeds, acidity, brix, pH, number of fallen flowers buds, number of abscised immature pods and number of witches-brooms.